The Aberdeen Kayak and its Congeners (Proceedings of the Society of Antiquaries of Scotland, 1912)
The Aberdeen 'kayak' has much in common with an example preserved at Edinburgh. At the present day, the kayak is in use over a great extent of the Arctic regions, from East Greenland westward across Arctic America, and along some 800 miles of the Asiatic coast, both westward and south-westward from Bering Straits. The Aberdeen example is made of four seal skins stretched over a slender framework of wood. With the kayak are a paddle, a spear, a bird-spear, a throwing-stick, and a harpoon. All are made of redwood with bone and ivory mountings. Traditionally the kayak is thought to have been recovered some time between 1690 and 1710.